Structural characterization of an Arf dimer interface: molecular mechanism of Arf‐dependent membrane scission. Issue 14 (31st May 2020) - Diestelkoetter‐Bachert, Petra; Beck, Rainer; Reckmann, Inge; Hellwig, Andrea; Garcia‐Saez, Ana; Zelman‐Hopf, Monika; Hanke, Anton; Nunes Alves, Ariane; Wade, Rebecca C.; Mayer, Matthias P.; Wieland, Felix
Abstract : Dimerization of the small GTPase Arf is prerequisite for the scission of COPI‐coated transport vesicles. Here, we quantify the monomer/dimer equilibrium of Arf within the membrane and show that after membrane scission, Arf dimers are restricted to donor membranes. By hydrogen exchange mass spectrometry, we define the interface of activated dimeric Arf within its switch II region. Single amino acid exchanges in this region reduce the propensity of Arf to dimerize. We suggest a mechanism of membrane scission by which the dimeric form of Arf is segregated to the donor membrane. Our data are consistent with the previously reported absence of dimerized Arf in COPI vesicles and could explain the presence of one single scar‐like noncoated region in each COPI vesicle. Abstract :